Neuron-Schwann cell interactions in peripheral nervous system homeostasis, disease, and preclinical treatment - Oliveira, Julia Teixeira; Yanick, Christopher; Wein, Nicolas; Gomez Limia, Cintia Elisabeth (Frontiers in Cellular Neuroscience, 2023)
Schwann cells (SCs) have a critical role in the peripheral nervous system. These cells are able to support axons during homeostasis and after injury. However, mutations in genes associated with the SCs repair program or myelination result in dysfunctional SCs. Several neuropathies such as Charcot–Marie–Tooth (CMT) disease, diabetic neuropathy and Guillain–Barré syndrome show abnormal SC functions and an impaired regeneration process. Thus, understanding SCs-axon interaction and the nerve environment in the context of homeostasis as well as post-injury and disease onset is necessary. Several neurotrophic factors, cytokines, and regulators of signaling pathways associated with proliferation, survival and regeneration are involved in this process. Preclinical studies have focused on the discovery of therapeutic targets for peripheral neuropathies and injuries. To study the effect of new therapeutic targets, modeling neuropathies and peripheral nerve injuries (PNIs) in vitro and in vivo are useful tools. Furthermore, several in vitro protocols have been designed using SCs and neuron cell lines to evaluate these targets in the regeneration process. SCs lines have been used to generate effective myelinating SCs without success. Alternative options have been investigated using direct conversion from somatic cells to SCs or SCs derived from pluripotent stem cells to generate functional SCs. This review will go over the advantages of these systems and the problems associated with them. In addition, there have been challenges in establishing adequate and reproducible protocols in vitro to recapitulate repair SC-neuron interactions observed in vivo. So, we also discuss the mechanisms of repair SCs-axon interactions in the context of peripheral neuropathies and nerve injury (PNI) in vitro and in vivo. Finally, we summarize current preclinical studies evaluating transgenes, drug, and novel compounds with translational potential into clinical studies.